PENERAPAN GOOD DAIRY FARMING PRACTICE (GDFP) DAN PENDAPATAN USAHA TERNAK SAPI PERAH KEMITRAAN DAN MANDIRI DI KABUPATEN JEMBER - Siti Aminah; M . Rondhi (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2019)
ABSTRACT Increased demand of milk is higher along with the increasing number of population, but increased demand of milk is less offset by increased production of local dairy cow milk so that in fulfilling local milk need is still doing a lot of milk import. With the existing of milk demand, livestock farming development of dairy cows can be done in Jember Regency. One of dairy cow farming in Jember Regency is located in Kemuning Lor Village Arjasa District Jember Regency which is the independent farm. Partnership farm in Jember Regency is in Ajung Village Ajung District, Balung Lor Village Balung District and Rowotengah Village Sumberbaru District which are partnership farm with Galur Murni Cooperative. Both livestock businesses experience the same problem which is the lows of milk production so that causes the lows of income received by the farmer. Milk production can increase if the farmer can apply GDFP (Good Dairy Farming Practice) of good dairy cows. This research aimed to (1) find out GDFP implementation, (2) find out the income, and (3) find out cost use efficiency. This research showed that: (1) The level of GDFP implementation of partnership farm was higher than the level of GDFP implementation of the independent farm. (2) Both livestock businesses of partnership and independent farm in Jember Regency is mutual. The amount of income per tail of partnership dairy cows was IDR 8,895,762/year and the net income per tail of independent dairy cows was IDR 11,635,231/year, (3) The cost use efficiency on partnership and independent dairy farm businesses was all efficient. The efficiency value of the R/C ratio of partnership dairy farm business was 1.25 while the efficiency value of the R/C ratio of the independent dairy farm was 1.18. Keywords: Dairy Cows, GDFP Implementation, Income, Efficiency of R/C Ratio